Football as a professional sport, and the prospects for its development in Ukraine - Berezka, S. M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The aim of the study was to determine the features of the functioning of European football as a segment of the service industry, bringing economic, social and political effects. The features of professional sports in Ukraine by the example of football as an object of scientific analysis were considered. It is considered the features of the functioning of football. The study used methods of system analysis, analysis methods specific sources, methods comparison, and statistical methods. It is shown that a significant influence on the development of modern sport in particular football by processes of commercialization and professionalization. Found that football is the manufacturer of a wide range of services that bring significant economic, social and political impact of the subjects and has a high football information and entertainment value for the audience.